Digital Tax Regulation in Facing Society 5.0 Era to Realize Indonesian Tax Sovereignty - Cahyadini, Amelia; Safiranita, Tasya; Muttaqin, Zainal; Fauzi, Rizki; Ramli, Ahmad M (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
Technological advancements have catalyzed the emergence of the digital economy, where digital platforms, leveraging internet access, can penetrate multiple regions and accrue substantial profits unrestricted by national jurisdictions. This scenario presents advantages and convenience but simultaneously challenges a country's tax sovereignty. The traditional tax system, predicated on a company's physical presence for tax liability, finds itself ill-equipped to handle the digital domain's nuances. This research seeks to explore the potential and hurdles in implementing digital taxes in Indonesia, delving into the government's regulatory efforts within the framework of Society 5.0. From an academic standpoint, digital taxes illustrate the disruption in tax collection due to the absence of a tangible company presence. Thus, this study also aims to investigate the determination of tax sovereignty in the context of digital taxation, aspiring to enrich scholarly discourse. Employing a normative juridical approach, this study scrutinizes legal norms and rules while considering empirical facts from the field. The findings indicate that while the introduction of digital taxes in Indonesia holds significant promise and faces considerable challenges, governmental action to update and streamline digital tax regulations is imperative. Furthermore, the principles underlying digital tax proposals, such as Pillar One, require reinforcement to enhance their effective implementation.DOI: https://doi.org/10.22304/pjih.v11n1.a7